PROCEEDINGS OF THE TWELFTH ANNUAL CONVENTION. - Bickell, Ralph T.; Kohler, E.L.; Scovill, H.T.; Kester, R.B.; Stevenson, R.A.; Adams, James P.; Meyer, H.G.; Elwell, F.H. (The Accounting Review, 1928)
Abstract The article focuses on the proceedings of the twelfth annual convention of the American Association of University Instructors in Accounting, held at Washington D.C., between December 28 and 29, 1927. After some introductory remarks by the organizers, papers were read by W. W. Nissley of the American Institute of Accountants, John R. Wildman of the company Haskins and Sells, David Himmelblau of Northwestern University, Evanston, Illinois, William A. Paton of the University of Michigan, Ann Arbor, Michigan, and J. L. Dohr of Greene and Hurd and of Columbia University, New York, New York. The second program meeting was given over to a discussion of various features of the federal income tax law. Johns Hopkins University's, Baltimore, Maryland, professor presided at the session and opened it with a brief statement introducing the speakers of the afternoon, all of whom were representatives of the Bureau of Internal Revenue. The third program session consisted of a joint meeting with the American Association of Collegiate Schools of Business. The general topic for discussion was "The Place of Accounting in Commerce Curriculum."